ANALISIS KINERJA KEUANGAN PADA KOPERASI SIMPAN PINJAM PESISIR UTAMA - Irmba Mbae (Fakultas Ekonomi Universitas Sintuwu Maroso, 2013)
This study aims to analyze the financial performance using Against Equity Ratio Total Assets , Independence and Asset Profitability Growth and Independence and Profitability Growth Equity in 2011,2012,2013 . The data used in this study are primary data and secondary data obtained through interviews (interviuw) , observation and documentation . Data were analyzed by using the method of financial ratio analysis.Results of research on the financial performance of Coastal Credit Unions Main with profitability ratio, in terms of the Equity Ratio Calculation Of Total Assets in 2011-2013 in view of the average calculation of 57% ( ≥ 20 % ) then the value is 100 , and scores for own capital ratio against total assets was 5.0 means it shows Cooperative located on Healthy Conditions . Independence and Asset Profitability Growth in Major Coastal Credit Unions in 2011-2013 viewed from an average of 8.7 % at 7.5 -10 scored 75, with a score of 2.25 this indicates Simply Health Cooperative condition. Independence and Profitability Growth Equity in Kopeasi Savings and Loans in 2011-2013 Main Coastal seen from an average of 6.2 % at 7.5 ≤ 5 × ˂ scored 50 , with a score of 1.50 in this case shows Cooperative Less healthy condition.Keyword : financial performance, financial ratio analysis.